How to Understand Climate Change as a Threat Multiplier in the Arctic - Knutsen, Bjørn Olav; Pedersen, Marius (Arctic Review on Law and Politics, 2024)
The aim of this paper is to analyse climate change as a threat multiplier to security dilemmas in the Arctic. Security dilemmas occur when one state’s efforts to enhance its security provokes reactions from other states, potentially leading to less security for all states involved. In an era of growing great power competition and confrontation, climate change might be a threat multiplier. This article contributes to our understanding of Arctic security dynamics by conducting a set of semi-structured interviews with mainly Norwegian civilian and military personnel on possible security dilemmas because of climate change. By applying Robert Jervis’ approach to security dilemmas, we ask how climate change affects how NATO and Russia interact in this area and how climate change might cause actors to pursue more offensive strategies in the north at the expense of defensive ones. By analysing state actors, day-to-day operations, and exercises, we conclude that climate change is poised to tilt the offence-defence balance not in favour of offensive strategies, but rather towards an offence-defence balance. We therefore conclude that there is no traditional security dilemma that may be exacerbated by climate change. Instead of exacerbating a security dilemma, climate change may precipitate one.